Knowledge and attitude survey regarding pain among nurse students of selected colleges in Biratnagar - Subba, Dipty; Subba, Neela (Nepalese Journal of Biosciences, 2015)
Pain is the most common reason why people seek medical attention. Nurses are the professionals who spend more time and round the clock with patient than any other member of health care professions. Pain management is a priority in nursing care but nursing students often find it a challenge. That is why nurse must possess the basic knowledge to identify the presence of pain in patients, to measure its intensity and make the steps necessary for treatment. Nursing students must be adequately prepared, in terms of knowledge and skill, to manage pain. For that nurse educators need to understand nursing students' pain knowledge and attitudes in order to design interventions to enhance their readiness for pain management. Therefore, a descriptive cross-sectional study was conducted to investigate the knowledge and attitudes regarding pain. The “Knowledge and Attitudes Survey Regarding Pain” tool was applied to 64 post basic bachelor nursing students by convenient purposive sampling from one private and one Government College. The data was analyzed using descriptive and inferential statistics. The age of the respondents ranges from 19 to 32 years with the mean age of 24.23 years. Most of the nurses are from ICU ward and have more than 2 years of working experience. The result of the study showed that many of the respondents 70.31% (n=45) were having poor knowledge regarding pain, mostly knowledge regarding the pharmacological aspect (80%) were found insufficient and perception of patient’s pain (60%). There is a need to give much attention on pain management in nursing curricula because nurses performed an instrumental role in the assessment and evaluation of pain.